The History of Reading
XIX, 222 p.
Keywords: Bringing together research from a variety of countries and periods, this volume introduces readers to the diverse approaches used to recover the evidence of reading through history in different societies, and asks whether reading practices are always conditioned by specific local circumstances or whether broader patterns might emerge.